Phenotypic and genetic relationships among temperament, immune, and carcass traits in beef cattle - Bates, Kerri E. (Kansas State University, 2013)
Cattle temperament has historically influenced selection decisions due to ease of handling. However, temperament may also influence economically relevant traits. The purpose of this study was to investigate relationships between temperament, Bovine Respiratory Disease (BRD) incidence, and resulting carcass merit in feedlot steers. Across a two year period, 2,870 crossbred steers were shipped from a single ranch source to a feedlot. At the time of feedlot placement, as well as at the time of reimplantation, temperament was measured via chute score (CS) and exit velocity (EV). Blood samples were taken upon arrival to the feedlot to determine circulating concentrations of interleukin 8 (IL-8) and cortisol, both of which are involved in immune function. Performance traits, including weight and gains, were measured at feedlot placement (d 0), reimplantation (d 73-100), and again 59 to 70 days later. Recorded carcass data included HCW (HCW), USDA yield grade (YG), marbling score (MS), ribeye area, and lung scores. Phenotypic statistical analysis was performed with SAS statistical software (SAS Inst., Inc., Cary, NC) and genetic parameters were estimated using ASREML (Ver. 3.0, VSN International, Ltd., Hemel Hempstead, UK). The pedigree file included records of 7,177 animals with up to 7 generation of pedigree. Contemporary group (CG, n=11) included initial ranch unit, date of arrival to the feedlot, feedlot pen, and processing dates. Fixed effects included in the model were pre-feedlot entry BRD treatment and CG. Cattle with higher CS at placement subsequently had more BRD incidence (P < 0.01). There was a positive phenotypic correlation between placement CS and blood cortisol concentrations (r = 0.07; P< 0.01), and cattle with higher cortisol concentration contracted BRD more often than their calmer peers (P < 0.05). Circulating IL-8 concentration had no influence on feedlot health. At the time of reimplantation, cattle that had been treated for BRD in the feedlot had lower chute scores (P < 0.001). Heritability estimates for CS at placement, EV at placement, CS at reimplantation, and EV at reimplantation were 0.23, 0.17, 0.19, and 0.27, respectively. BRD incidence had a negative genetic correlation with all measures of temperament recorded at the second processing period.
Keywords: Beef cattle; BRD; Carcass; Temperament; Agriculture, General (0473); Animal Diseases (0476); Animal Sciences (0475)